2008
DOI: 10.1088/0953-2048/21/5/054015
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nb3Sn and MgB2wires

Abstract: The critical current density in industrial Nb 3 Sn and MgB 2 wires is currently optimized by introducing various kinds of additives, either Ta and/or Ti for Nb 3 Sn wires or SiC or C for MgB 2 wires. In the following, several problems linked to the presence of additives in the two classes of compounds are discussed.A reinvestigation of the site occupancy of Ta and Ti additives in Nb 3 Sn wires shows that the Ta atoms occupy the 6c chain sites, while the Ti atoms are located on the cubic 2a sites. It follows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…This procedure has been successfully used in the case of wires, polycrystalline samples, and crystals. [70][71][72][73] However, if pinning is ruled only by defects whose dimensions are smaller than the intervortex distance, it is expected J 1/2 c ∝ (1 − h). 67 In this case, H irr may be determined by doing a linear extrapolation down to zero of the J These results indicate that, for the single crystal sample B, the pinning mechanisms are ruled by defects whose dimensions are smaller that the intervortex distance in the investigated field range and as a consequence, the most appropriate procedure for determining H irr (T ) is from the J 1/2 c vs H curve.…”
Section: A Vortex Pinning Propertiesmentioning
confidence: 99%
“…This procedure has been successfully used in the case of wires, polycrystalline samples, and crystals. [70][71][72][73] However, if pinning is ruled only by defects whose dimensions are smaller than the intervortex distance, it is expected J 1/2 c ∝ (1 − h). 67 In this case, H irr may be determined by doing a linear extrapolation down to zero of the J These results indicate that, for the single crystal sample B, the pinning mechanisms are ruled by defects whose dimensions are smaller that the intervortex distance in the investigated field range and as a consequence, the most appropriate procedure for determining H irr (T ) is from the J 1/2 c vs H curve.…”
Section: A Vortex Pinning Propertiesmentioning
confidence: 99%
“…The difference is due to the fact that Ta replaces Nb and Ti replaces Sn in the Nb 3 Sn lattice (suggested in Ref. 105 and confirmed by Ref. 106).…”
Section: Bottura and A Godekementioning
confidence: 83%
“…In experiments by Goldacker et al [134,135], it was observed that the martensitic transformation in stoichiometric Nb 3 Sn could be prevented through various additions, including tantalum, titanium, nickel, gallium, and hydrogen. The martensitic transformation was completely suppressed in samples with 0.6 at.% H, 2.8 at.% Ta, 1.3 at.% Ti, and 1 at.% Ni, with normal state resistivities of 37 µΩcm, 29 µΩcm, 33 µΩcm, and 30 µΩcm, respectively.…”
Section: Literature On the Martensitic Transformationmentioning
confidence: 99%